2015
DOI: 10.1186/s12967-015-0474-4
|View full text |Cite
|
Sign up to set email alerts
|

CXCL13, CCL4, and sTNFR as circulating inflammatory cytokine markers in primary and SLE-related autoimmune hemolytic anemia

Abstract: BackgroundA considerable proportion of autoimmune hemolytic anemia (AIHA) are secondary to underlying autoimmune disorders, especially syetemic lupus erythematosus (SLE), and the clinical and laboratory index for early discrimination between primary and SLE-related AIHA has yet to be defined. In the present study, we proposed novel cytokine patterns in the pathogenesis of AIHA as well as parameters for the timely identification of SLE-related patients.MethodsAIHA patients confirmed by immunohematology techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Selvaraj et al [76] showed a high expression of MIP-1β in monocytes activated from SDC patients compared to monocytes from healthy individuals. Wu et al [81] demonstrated in autoimmune hemolytic anemia that an elevated circulating level of MIP-1β indicates a boost in erythroid proliferation and reticulocytosis. It is possible that in SCA, this chemokine can be acting that way.…”
Section: Discussionmentioning
confidence: 99%
“…Selvaraj et al [76] showed a high expression of MIP-1β in monocytes activated from SDC patients compared to monocytes from healthy individuals. Wu et al [81] demonstrated in autoimmune hemolytic anemia that an elevated circulating level of MIP-1β indicates a boost in erythroid proliferation and reticulocytosis. It is possible that in SCA, this chemokine can be acting that way.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , CXCL13 induced production of proinflammatory factors (CXCL1, CXCL12, MIF, and LIF) in human podocytes, which indicated that CXCL13 was closely related to renal inflammation [ 19 , 20 ]. Recently, CXCL13 has been reported to participate in SLE-related autoimmune hemolytic anemia [ 32 ]. We also found that the expression of CXCL13 was high in Chinese SLE patients especially in LN patients and it was positively correlated with SLEDAI especially with rSLEDAI.…”
Section: Discussionmentioning
confidence: 99%
“…Of 15 articles having AIHA/DAT as their main topic, 10 provided a clear definition of AIHA [9,19,29,46,47,49,53,57,61] whereas five provided an incomplete or no definition of AIHA [43,48,62,64]. Further, of 42 articles not having AIHA as their main topic, only nine provided a clear definition.…”
Section: Clinical Definitionsmentioning
confidence: 99%